زكاة المال عن الصغير والمجنون - دراسة مقارنة ما بين الفقه الإسلامي والقانون الليبي: Zakat for Children and Insane - A comparative study between Islamic jurisprudence and Libyan law - Gaddour, Aiman M Omar; Abdul Shukor, Syahirah; Hussin, Syaryanti (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
زكاة المال مكانة عظيمة في الإسلام، ففضلا عن وجوبها، فإنها عبادة مالية، فهي طهارة ونماء وزيادة وصلاح وبركة، وموردا للدولة، وإشاعة روح التكافل والتضامن ما بين أفراده، وفي ليبيا؛ فقد نظم المشرع شروطها، وأحكامها، ومصاريفها بموجب القانون رقم "13" لسنة 1991 بشأن الزكاة، إلا أن الواقع العملي كشف عن إشكالية البحث المتمثلة في قصور هذه القانون، عن معالجة بعض المسائل؛ ومنها حكم زكاة المال في مال الصغير أو المجنون ومن في حكمهما، وهنا تظهر أهمية البحث؛ خاصة؛ أنها تمس طائفة كبيرة من الشعب، وانعكاس ذلك على أحد أهم موارد الدولة المالية، وقد أعتمد الباحث المنهج الوصفي التحليلي، المقارن بالفقه الإسلامي، باستقراء النصوص القانونية، والفقهية، وأدلته التفصيلية، وبيَّان عللها الشرعية، وصولا لهدف البحث المتمثل في استجلاء الحكم القانوني والشرعي لزكاة المال في مال الصغير والمجنون ومن في حكمهم، وقد خلص الباحث لنتيجة تؤكد خلو القانون الليبي من نص صريح يحكم زكاة مال الصغير، واختلاف الفقه الإسلامي بشأن حكمها، خالصا إلى التوصية بوجوب التدخل التشريعي بالنص صراحة على حكمها. Charity (zakat) has a great place in Islam. As it is obligatory, it is also a financial worship. It is considered as a purity, growth, increase, righteousness, blessing, and a resource for a country. It spreads a spirit of solidarity among society members. In Libyan setting, the legislator regulates its terms, conditions, and expenses. However, the practical reality revealed that there is shortage and inadequacy in its regulations and laws especially in dealing with some issues such as ruling of charity (zakat) regarding to (al-Saghir) (Ghair Mukalif) the under-puberty people’s money or the insane people’s money. Thus, the significance of the research resides in its dealing with such a wide range of people, and its reflection on one of the most important financial resources of the country. The researcher has adopted the descriptive analytical approach, compared to Islamic jurisprudence, by extrapolating the legal and jurisprudential texts, and its detailed evidence, and explaining their legitimate reasons, in order to achieve the research goal by clarifying the legal and legitimizing rulings for charity of such kind of peoples. The researcher come up with a conclusion confirms that the Libyan law is devoid of an explicit text governing the charity (zakat) of (al-Saghir) (Ghair Mukalif) the under-puberty people’s money or the insane people’s money, and the difference in Islamic jurisprudence regarding their ruling. The study recommends the necessity of legislative intervention by explicitly stipulating its ruling.